On a Periodic System of Difference Equations - Stevo Stević; Josef Diblík; Bratislav Iričanin; Zdeněk Šmarda (Abstract and Applied Analysis)
Here we give a very short and elegant proof of an extension of two recent results on global periodicity of two systems of difference equations in a work of Elsayed et al. 2012.